Pengaruh Edukasi Video Animasi Terhadap Tingkat Pengetahuan Personal Hygiene Pada Anak di SD Muhammadiyah Warungboto Yogyakarta - Ferianto; Hidayah, Nurul (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Personal hygiene, as an essential aspect of self-care, is a key determinant of health. In children, personal hygiene encompasses the maintenance of oral and dental health, hand and nail hygiene, care of the hair and scalp, as well as the cleanliness of clothing. Objective: This study aimed to evaluate the difference in personal hygiene knowledge among elementary school students before and after receiving health education through animated video media. Methods: A pre-experimental study with a one-group pretest–posttest design was conducted involving 54 students from grades 1 and 2 at SD Muhammadiyah Warungboto, Yogyakarta, selected using a total sampling technique. Data were collected through questionnaires and analyzed using univariate analysis: frequency distribution to describe the characteristics of respondents and research variables and bivariate analysis: marginal homogeneity test to assess changes in knowledge levels. Results: Prior to the intervention, the majority of respondents (n = 43; 79.6%) demonstrated inadequate knowledge of personal hygiene. Following the intervention, most participants (n = 46; 85.2%) showed improved knowledge. Statistical analysis using the marginal homogeneity test revealed a significant difference (p = .000 < 0.05), indicating that the animated video education effectively enhanced students’ understanding of personal hygiene. Conclusion: Health education delivered through animated video media has a significant positive impact on improving personal hygiene knowledge among elementary school children at SD Muhammadiyah Warungboto, Yogyakarta.